Progresses on two-phase modeling of proton exchange membrane water electrolyzer - Boshi Xu; Tao Ouyang; Yang Wang; Yang Yang; Jun Li; Liangliang Jiang; Chaozhong Qin; Dingding Ye; Rong Chen; Xun Zhu; Qiang Liao (Energy Reviews, 2024)
The Proton Exchange Membrane (PEM) water electrolyzer is considered one of the promising energy storing means for harnessing variable renewable energy sources to produce hydrogen. Understanding the internal fluid dynamics, which are often challenging to directly observe experimentally, has prompted the use of numerical models to investigate two-phase flow within PEM water electrolyzers. In this study, we provide a comprehensive review of prior research focusing on two-phase modeling of PEM electrolyzers, encompassing both components at mesoscopic scales and the full electrolyzer at the macroscopic level. We delve into the specifics of various modeling approaches for two-phase flow at different scales and summarize and discuss the current state of the art in the field. Presently, two-phase models for the full electrolyzer predominantly employ a macroscopic homogeneous assumption. However, mesoscopic and microscopic models capable of tracking phase interfaces are limited to components. Challenges persist in integrating various modeling scales into a comprehensive electrolyzer model, particularly in coupling two-phase flow between the channels and porous media. Future efforts should focus on developing multi-scale models and simulating two-phase flow under fluctuating input conditions. Additionally, given the structural similarities between PEM water electrolyzers and PEM fuel cells, we compare and discuss differences in two-phase modeling between the two technologies. This work offers the insights for researchers in the field of modeling of PEM water electrolyzers and even fuel cells.